IN VITRO DETERMINATION OF ANTIOXIDANT ACTIVITY OF PHYSALIS ANGULATA LNN. - MURALI KRISHNA T; RAJENDER VADLURI; E. MANOJ KUMAR (International Journal of Pharma and Bio Sciences, 2013)
The present investigation was carried out to determine the antioxidant properties in methanolic extract of leaves, stem, fruit and roots of Physalis angulata (L). The antioxidant assay was carried out using free radicals DPPH, superoxide, nitric oxide, hydrogen peroxide and hydroxyl radical. Among the extracts tested fruit and leaf extracts were found to be significant in their antioxidant property than stem and roots. However, amounts of total phenolic and flavanoid content were high in leaves and fruit extracts.